GE_GERICHTE C/3529/2014 vom 10. August 2018 - GE Cour de justice (2018)
ACTION EN RESPONSABILITÉ ; LÉSION CORPORELLE ; LIEN DE CAUSALITÉ ; PREUVE ; DOMMAGE MÉNAGER ; MOTIVATION DE LA DEMANDE | CO.41; CO.46.al1; CO.42.al1; CC.8